A new data offloading algorithm by considering interactive preferences - Mohammad Hatami, Amir; Mirmohseni, Mahtab; Ashtiani, Farid (2016 IEEE 27th Annual International Symposium on Personal, Indoor, and Mobile Radio Communications (PIMRC), 2016)
In this paper, we propose a data offloading algorithm in a network comprised of a macro base station and a few number of WiFi access points with overlapped coverage areas. The main goal of our algorithm is how to assign offloaded mobile stations (MSs) to access points (APs). Our approach in proposing the algorithm is based on mapping the problem onto finding a suitable matching algorithm, in order to minimize the average delay of the offloaded packets as one of the main QoS parameters on the one hand and to maximize the utility of the APs on the other hand. The utility of each AP is considered to be a combination of monetary benefit due to offloading service and the cost due to extra energy consumption. Since the preferences over APs from the viewpoint of MSs are dependent on each other, our problem is in fact a matching problem with externalities. Thus, in order to obtain a suitable matching, we apply swap matching algorithm to reach a final matching satisfying two-sided exchange stability. Our numerical results show the superiority of our proposed algorithm when compared to two simple assigning algorithms based on maximum SNR and traffic load balancing.